Setting Preconception Care Priorities in Australia Using a Delphi Technique - Boyle, Jacqueline A.; Black, Kirsten; Dorney, Edwina; Amor, David J.; Brown, Louise; Callander, Emily; Camilleri, Renea; Cheney, Kate; Gordon, Adrienne; Hammarberg, Karin; Jeyapalan, Dheepa; Leahy, Deana; Millard, Jo; Mills, Catherine; Musgrave, Loretta; Norman, Robert J.; O'Brien, Claire; Roach, Vijay; Skouteris, Helen; Steel, Amie; Walker, Sue; Walker, Ruth (Seminars in Reproductive Medicine, 2022)
Preconception health affects fertility, pregnancy, and future health outcomes but public awareness of this is low. Our aims were to rank priorities for preconception care (PCC), develop strategies to address these priorities, and establish values to guide future work in preconception healthcare in Australia. A Delphi technique involved two rounds of online voting and mid-round workshops. Inputs were a scoping review of PCC guidelines, a priority setting framework and existing networks that focus on health. During July and August, 2021, 23 multidisciplinary experts in PCC or social care, including a consumer advocate, completed the Delphi technique. Ten priority areas were identified, with health behaviors, medical history, weight, and reproductive health ranked most highly. Six strategies were identified. Underpinning values encompassed engagement with stakeholders, a life course view of preconception health, an integrated multi-sectorial approach and a need for large scale collaboration to implement interventions that deliver impact across health care, social care, policy and population health. Priority populations were considered within the social determinants of health. Health behaviors, medical history, weight, and reproductive health were ranked highly as PCC priorities. Key strategies to address priorities should be implemented with consideration of values that improve the preconception health of all Australians.
Keywords: preconception care; primary care; health care; consensus